2020
DOI: 10.3892/ol.2020.11798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a five‑gene signature for predicting the progression and prognosis of stage I endometrial carcinoma

Abstract: Uterine corpus endometrial carcinoma (UCEC) is often diagnosed at an early clinical stage based on abnormal vaginal bleeding. However, the prognosis of UCEC is poor. The present study was conducted to identify novel tumor grade-related genes with the potential to predict the prognosis and progression of UCEC. A total of three gene expression microarray datasets were downloaded from the Gene Expression Omnibus database, and one RNA-sequencing dataset with corresponding clinical information of patients with UCEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Although the study of UCEC treatment has made some progress [41], the mortality continues to rise, seriously threatening women's health. Many markers that can predict the prognosis of UCEC have been found [42]; however, so far, there is no unified index. lncRNAs have the potential to become immunotherapeutic targets and biomarkers for a UCEC prognosis due to the characteristics of its high efficiency, high tissue specificity, and high stability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study of UCEC treatment has made some progress [41], the mortality continues to rise, seriously threatening women's health. Many markers that can predict the prognosis of UCEC have been found [42]; however, so far, there is no unified index. lncRNAs have the potential to become immunotherapeutic targets and biomarkers for a UCEC prognosis due to the characteristics of its high efficiency, high tissue specificity, and high stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found gene prognostic markers closely related to UCEC (68)(69)(70), but it is the first time to construct a model in Treg cells to predict the prognosis of UCEC. AUC is a crucial standard to judge whether a prediction model has good discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Depth of myometrial invasion and lymphovascular space invasion is the main predictor of prognosis after surgery ( Brooks et al, 2019 ). During the past decade, considerable progress has been made in understanding the complex molecular and cellular nature of EC, and various key genes have been identified through bioinformatic analyses ( Huo et al, 2019 ; Bian et al, 2020 ; Liu et al, 2020 ). Through WGCNA, we determined the most significant modules using clinical traits.…”
Section: Discussionmentioning
confidence: 99%